Two new insulator proteins, Pita and ZIPIC, target CP190 to chromatin - Maksimenko, Oksana; Bartkuhn, Marek; Stakhov, Viacheslav; Herold, Martin; Zolotarev, Nickolay; Jox, Theresa; Buxa, Melanie K.; Kirsch, Ramona; Bonchuk, Artem; Fedotova, Anna; Kyrchanova, Olga; Renkawitz, Rainer; et al. (Genome Research, 2015)
Insulators are multiprotein–DNA complexes that regulate the nuclear architecture. The Drosophila CP190 protein is a cofactor for the DNA-binding insulator proteins Su(Hw), CTCF, and BEAF-32. The fact that CP190 has been found at genomic sites devoid of either of the known insulator factors has until now been unexplained. We have identified two DNA-binding zinc-finger proteins, Pita, and a new factor named ZIPIC, that interact with CP190 in vivo and in vitro at specific interaction domains. Genomic binding sites for these proteins are clustered with CP190 as well as with CTCF and BEAF-32. Model binding sites for Pita or ZIPIC demonstrate a partial enhancer-blocking activity and protect gene expression from PRE-mediated silencing. The function of the CTCF-bound MCP insulator sequence requires binding of Pita. These results identify two new insulator proteins and emphasize the unifying function of CP190, which can be recruited by many DNA-binding insulator proteins.